AB0620 High risk of mistaken classification of primary antiphospholipid syndrome as systemic lupus erythematosusaccording to the slicc criteria: analysis of a cohort of 214 antiphospholipid patients. (12th June 2018) - Paule, R.; Costedoat-Chalumeau, N.; MOREL, N.; LE GUERN, V.; Fredi, M.; Coutte, L.; Belhocine, M.; Mouthon, L.; Le Jeunne, C.; Chauvin, A.; Piette, J.-C.
Abstract : Background: The diagnosis of systemic lupus erythematosus (SLE) is based on the association of clinical and biological manifestations and on clinical experience. In 2012, a major revision by the Systemic Lupus International Collaborating Clinics (SLICC) group sought to improve their sensitivity and specificity. In replications, the SLICC classification produced fewer errors than the previous version; its higher sensitivity but lower specificity meant that some patients could be classified with SLE although they had another disease. In fact, the distinction between PAPS, APS associated with SLE, and isolated SLE may be difficult in some cases because the two diseases share some clinical and biological manifestations. Objectives: To assess the limitations of the SLICC (Systemic Lupus International Collaborating Clinics) classification criteria for systemic lupus erythematosus (SLE), in patients with primary antiphospholipid syndrome (PAPS). Methods: Retrospective study of a cohort of APS patients (Sydney criteria). We successively excluded patients with 1 at least one "SLE-specific" manifestation (biopsy-proven SLE nephropathy, arthritis, cutaneous, or neurologic SLE manifestations, pericarditis, autoimmune haemolytic anaemia, oral and nasal ulcers, non-scarring alopecia, anti-dsDNA, and anti-Sm antibodies), 2 any other autoimmune connective tissue disease, and/or 3 antinuclear antibodies>1/320. Careful file review confirmed PAPS among the remaining patients. We then assessed the number of SLICC criteria each patient met. Results: Among these 214 APS patients, we excluded 85 with at least one SLE-specific manifestation, 8 with another connective tissue disease, and 21 with antinuclear antibodies>1/320, leaving 100 patients with primary APS. Among them, 28% met at least 4 SLICC classification criteria including one clinical and one immunological criterion (antiphospholipid antibodies, aPL, by definition) and could thus theoretically be classified with SLE. Fourteen had an arterial phenotype (50%), 9 a history of catastrophic APS (32%), and 18 a triple-positive profile for aPL (64%). None had developed SLE during a median follow-up of 12 [6.5–17] years. Conclusions: Because 28% of our patients with longstanding and strictly defined PAPS could be mistakenly classified as SLE, they were at risk of deleterious therapeutic management. We therefore suggest that any future classification for SLE should specifically require at least one SLE-specific criterion for patients with aPL. References: [1] Petri M, Orbai A-M, Alarcón GS, et al. Derivation and validation of the Systemic Lupus International Collaborating Clinics classification criteria for systemic lupus erythematosus. Arthritis Rheum2012;64:2677–86. doi:10.1002/art.34473 [2 ] Piette JC, Wechsler B, Frances C, et al. Exclusion criteria for primary antiphospholipid syndrome. J Rheumatol 1993;20 :1802–4. [3] Asherson RA, Khamashta MA, Ordi-Ros J, et al. The 'primary' antiphospholipid syndrome: major clinical and serological features. Medicine (Baltimore) 1989;68 :366–74. [4] Gómez-Puerta JA, Martín H, Amigo M-C, et al. Long-term follow-up in 128 patients with primary antiphospholipid syndrome: do they develop lupus? Medicine (Baltimore) 2005;84 :225–30. Disclosure of Interest: None declared